Crisponi/cold‐induced sweating syndrome: Differential diagnosis, pathogenesis and treatment concepts. Issue 1 (16th September 2019) - Buers, Insa; Persico, Ivana; Schöning, Lara; Nitschke, Yvonne; Di Rocco, Maja; Loi, Angela; Sahi, Puneet Kaur; Utine, Gulen Eda; Bayraktar‐Tanyeri, Bilge; Zampino, Giuseppe; Crisponi, Giangiorgio; Rutsch, Frank; et al.
Abstract: Crisponi/cold‐induced sweating syndrome (CS/CISS) is an autosomal recessive disease characterized by hyperthermia, camptodactyly, feeding and respiratory difficulties often leading to sudden death in the neonatal period. The affected individuals who survived the first critical years of life, develop cold‐induced sweating and scoliosis in early childhood. The disease is caused by variants in the CRLF1 or in the CLCF1 gene. Both proteins form a heterodimeric complex that acts on cells expressing the ciliary neurotrophic factor receptor (CNTFR). CS/CISS belongs to the family of "CNTFR‐related disorders" showing a similar clinical phenotype. Recently, variants in other genes, including KLHL7, NALCN, MAGEL2 and SCN2A, previously linked to other diseases, have been associated with a CS/CISS‐like phenotype. Therefore, retinitis pigmentosa and Bohring‐Optiz syndrome‐like ( KLHL7 ), Congenital contractures of the limbs and face, hypotonia, and developmental delay syndrome ( NALCN ), Chitayat‐Hall/Schaaf‐Yang syndrome ( MAGEL2 ), and early infantile epileptic encephalopathy‐11 syndrome ( SCN2A ) all share an overlapping phenotype with CS/CISS, especially in the neonatal period. This review aims to summarize the existing literature on CS/CISS, focusing on the current state of differential diagnosis, pathogenesis and treatment concepts in order to achieve an accurate and rapid diagnosis. This will improve patient management and enable specific treatments for the affected individuals. Abstract :